Teaching trauma: sexual violence and the kairotic space of the first-year writing classromm - Sharp, Kellie Jean (Trauma-informed pedagogy, 2022)
Using Margaret Price's concept of kairotic space, this chapter asserts that the first-year writing classroom is a particularly fitting place to explore topics like consent and sexual assault. However, I caution the importance of using a trauma-informed approach to these topics. I provide an overview of the distinctions between related fields: trauma-informed pedagogy, trauma theory, and disability studies in order to argue for a pedagogical approach that takes each into account. First-year writing instructors, as well as other instructors in the university, should strive to live in the discomfort that often emerges from difficult material not only because it is necessary for building a better society but also because it is pedagogically sound. Furthermore, I argue that in order to have a truly trauma-informed approach, we need to change the very foundations of the university.